Etnomuzykologia Solidarności. Wokół "Musical Solidarities: Political Action and Music in Late Twentieth-Century Poland" Andrei F. Bohlman - Kwapień, Joanna (Res Facta Nova, 2021)
The article discusses the book Musical Solidarities by Andrea F. Bohlman. In her monograph she describes the history of Solidarity, placing sound at the centre of her analysis. The methods she uses allow her to examine historical facts holistically: she reaches for fieldwork as well as voice analysis, specific music motifs, and the influence of Polish musicians and composers on social attittudes in the 1980s. She offers an interesting analysis of the songs that acompanied the protests and the phenomenon of Stefan Bratkowski’s “Gazeta Dźwiękowa” [Sound Gazette] and its influence on the listeners. She draws attention to the icons of the Solidarity period such as Father Jerzy Popiełuszko, Lech Wałęsa, Krzysztof Penderecki and their voices, understood both literally and metaphorically. She also analyses contemporary reinterpretations of songs from that period, using Jacek Kaczmarski’s Mury [Walls] and Janek Wiśniewski padł [Janek Wiśniewski fell]. The author rejects the chronological approach to research, analysing the historical period through problematization of selected issues.